Correlation between age and the sciatic nerve diameter in the first 2 years of life: A high‐resolution ultrasound study - Jenny, Carole; Linde, Jacoba; Hundsberger, Thomas; Broser, Philip J. (Brain and behavior, 2023)
Aim To investigate the maturation of the peripheral nervous system by analyzing the cross‐sectional area of the sciatic nerve during the first 2 years of life. Methods The sciatic nerve was examined by high‐resolution ultrasound imaging in 52 children aged 0 days to 10 years, 45 of whom were younger than 2 years. The correlation between the cross‐sectional area of the nerve and the age was statistically tested. A logarithmic regression analysis was performed to develop a logarithmic growth model of the cross‐sectional area. Results There is a highly significant correlation between the age and the cross‐sectional area of the sciatic nerve. The growth rate can well be described by a logarithmic model. Interpretation Based on the literature on the maturation of the median nerve and nerve roots and the findings of the present study, we conclude that both the proximal and the distal parts of the nerves of the peripheral nervous system increase simultaneously. What this paper adds Normative values for the size of the sciatic nerve in children. The sciatic nerve was examined by high‐resolution ultrasound imaging in children younger than two years. There is a highly significant correlation between the age and the cross‐sectional area of the sciatic nerve. The growth rate can well be described by a logarithmic model.